Delivery of online adaptive magnetic resonance guided radiotherapy based on isodose boundaries. (April 2021) - Votta, Claudio; Cusumano, Davide; Boldrini, Luca; Dinapoli, Nicola; Placidi, Lorenzo; Turco, Gabriele; Antonelli, Marco Valerio; Pollutri, Veronica; Romano, Angela; Indovina, Luca; Valentini, Vincenzo
Abstract: Magnetic Resonance-guided Radiotherapy (MRgRT) allows direct monitoring of treated volumes. The aim of this study was to investigate the feasibility of a new gating strategy consisting in using an isodose as boundary. Forty-four patients treated for thoracic and abdominal lesions using MRgRT were enrolled. The accuracy of the new strategy was compared to the conventional one in terms of area improvement available for gating without compromising target coverage. A mean increase of 24% for lung, 15% for liver and 11% for pancreas was observed, demonstrating how the new method can be useful in challenging situations with low dose conformality.